AB0111 Cadmium nanoparticles citrullinate intracellular cytokeratins: cadmium potentially links rheumatoid arthritis to smoking and numerous working class occupations. (15th June 2017) - Hutchinson, D; Müller, J; McCarthy, JE; Gun'ko, Y; Verma, N; Bi, X; Cristo, L Di; Kickham, L; Movia, D; Prina-Mello, A; Volkov, Y
Abstract : Background: Smoking has emerged as a consistent risk factor for ACPA positive RA, although the specific constituents of cigarette smoke that induce citrullination are unknown. It has been hypothesised that cadmium triggers RA as its inhalation links various well established risk factors for RA such as smoking (the most important environmental source of cadmium) and numerous working class occupations [1]. Objectives: To determine whether the cadmium-derived materials induce intracellular citrullination. Methods: Human A549 lung epithelial cells were exposed to cadmium in ionic and particulate form represented by cadmium chloride and cadmium oxide, respectively, and their combinations with ultrafine carbon black (ufCB) nanoparticles produced following high temperature combustion, imitating cigarette burning. Protein citrullination in cell lysates was analysed by SDS-PAGE electrophoresis with western blotting and verified by immunofluorescence staining and confocal microscopy. Target citrullinated proteins were identified by proteomic analysis. Results: Cytotoxicity studies demonstrated that cadmium compounds were toxic to the cells. Based on the results of cytotoxicity measurements, all the materials utilised in the experiments were subsequently applied to the cells in sub-toxic concentrations. Cadmium oxide, ufCB and its combination with cadmium chloride and cadmium oxide after high temperature combustion induced citrullination of multiple proteins in cultured human lung epithelial cells of A549 cell line, as demonstrated by SDS-SDS-PAGE electrophoresis and western blotting. This phenomenon develops via a peptidylargininedeiminase-dependent mechanism, as demonstrated in our previous studies [2]. The majority of citrullinated proteins were represented by the bands corresponding to the molecular weights between 55 and 72 kDa, and several less abundant bands at the level of ∼25kDa and over 130 kDa. Acidic cytokeratins of type I (9, 10) and basic/neutral cytokeratins type II (1, 2, 5, 6A, 6B and 77) were identified as major intracellular citrullination targets. Immunofluorescent staining demonstrated that the citrullinated proteins were localised both in the cytoplasm and nuclei of cells exposed to cadmium particles, similar to the distribution patterns observed in cells exposed to ufCB. Conclusions: Cadmium nanoparticle exposure facilitates post-translational citrullination of proteins. References: Hutchinson D. Cadmium, one of the villains behind the curtain:has exposure to cadmium helped to pull the strings of seropositive rheumatoid arthritis pathogenesis all along? International journal of rheumatic diseases 2015;18:570–3. Mohamed BM, Verma NK, Davies AM, McGowan A, Crosbie-staunton K, Prina-Mello A, et al. Citrullination of proteins:a common post-translational modification pathway induced by different nanoparticles in vitro and in vivo. Nanomedicine 2012;7:1181–95. Acknowledgements: This work has been supported by the Higher Education Authority of Ireland, Science Foundation of Ireland through the Advanced Materials and BioEngineering Research (AMBER) project (Grant #SFI/12/RC/2278) and the Cornwall Arthritis Trust. Disclosure of Interest: None declared